2020
DOI: 10.1021/acsestengg.0c00076
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impeding Replacement of Ion Exchange with (Electro)Catalytic Treatment for Nitrate Removal from Drinking Water

Abstract: Nitrate (NO3 –) has impacted more groundwater supplies than any other pollutant in the world. It is currently removed at water treatment plants by ion exchange, which is effective but comes at a steep financial and environmental cost. (Electro)­catalytic treatment of nitrate has emerged as a promising alternative technology, which relies on reducing nitrate to dinitrogen gas or ammonium via reduction on a bimetal catalyst with atomic hydrogen oxidation. The bimetal catalyst contains a platinum group metal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 126 publications
0
37
0
Order By: Relevance
“…Pd-based catalysts with various formulations have been shown to continually lose activity over repeated cycles of catalytic nitrate or nitrite reduction, even though no major changes in physical characterizations were observed. 53,75,76 Heating the electrodes at moderate temperature in H 2 flow might help restore the activity. 51,75 Previous long-term studies in catalytic process also indicated the activity would eventually reach a steady state.…”
Section: Resultsmentioning
confidence: 99%
“…Pd-based catalysts with various formulations have been shown to continually lose activity over repeated cycles of catalytic nitrate or nitrite reduction, even though no major changes in physical characterizations were observed. 53,75,76 Heating the electrodes at moderate temperature in H 2 flow might help restore the activity. 51,75 Previous long-term studies in catalytic process also indicated the activity would eventually reach a steady state.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have mainly focused on understanding the mechanism of the anode while information on the reverse processes like the flow of e − from electrodes to microorganisms was insubstantial. In 2004, cathodic DET flow was reported for the reduction of various forms of nitrogen (nitrate NO 3 − to nitrite NO 2 − ) from the cathode and assured at about −0.34 V vs. SHE, it further enriched the substances along with microbial species [18,46,49]. Several Desulfovibrio sp.…”
Section: Transmission Of Electrons At the Cathodementioning
confidence: 99%
“…The catalytic method has been advanced to the point of using two different metals in the process to optimize NO 3 − reduction, with a catalytic metal (Cu, Pd, Pt, Ti) applied on a supporting metal such as Titanium (TiO 2 ) that aids and promotes the catalytic reduction, however, this seldom affords the reduction of NO 3 − to N 2 [101,102]. For treatment of large volumes of industrial wastewater, this method is very expensive to maintain and apply as a continuous remediation system [103]. Most chemical remediation approaches produce byproducts that require special disposal methods due to their potential to cause secondary contamination.…”
Section: Chemical Nitrate Remediationmentioning
confidence: 99%
“…− that are time-consuming to dispose, hence becoming an environmental burden and causing secondary contamination [103].…”
Section: Physical Nitrate Remediationmentioning
confidence: 99%